2020
DOI: 10.1089/mdr.2019.0235
|View full text |Cite
|
Sign up to set email alerts
|

A New Phage Cocktail Against Multidrug, ESBL-Producer Isolates of Shigella sonnei and Shigella flexneri with Highly Efficient Bacteriolytic Activity

Abstract: The globally increasing incidence of antibiotic resistance in pathogenic microorganisms such as Shigella, a cause of human acute gastrointestinal infections, calls for developing effective alternatives. In this study, the antibiotic resistance pattern, extended-spectrum b-lactamase (ESBL)-production, and molecular characteristics of 70 multidrug-resistant isolates belong to the two most frequent species of Shigella genus, that is, Shigella sonnei (44 isolates) and Shigella flexneri (26 isolates) were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…In other words, the anti-Shigella effect of the phages against the non-specific species could be considered as a complementary privilege guaranteeing a higher or even complete elimination of pathogens and preventing the formation of phage-resistant isolates through the synergistic effect of the specific phages. In our previous study, we reported the potential application of the bacteriolytic activity of a phage cocktail consists of vB_SflS-ISF001 and vB_SsoS-ISF002 against food and clinical Shigella isolates (Shahin et al 2019d(Shahin et al , 2020. Moreover, bacterial resistance against bacteriophages occurs through different mechanisms such as R/M, CRISPR-cas, defence genes encoded by plasmids or prophages.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, the anti-Shigella effect of the phages against the non-specific species could be considered as a complementary privilege guaranteeing a higher or even complete elimination of pathogens and preventing the formation of phage-resistant isolates through the synergistic effect of the specific phages. In our previous study, we reported the potential application of the bacteriolytic activity of a phage cocktail consists of vB_SflS-ISF001 and vB_SsoS-ISF002 against food and clinical Shigella isolates (Shahin et al 2019d(Shahin et al , 2020. Moreover, bacterial resistance against bacteriophages occurs through different mechanisms such as R/M, CRISPR-cas, defence genes encoded by plasmids or prophages.…”
Section: Resultsmentioning
confidence: 99%
“…The infection and lysis capacity of phages were determined using the spot test method, as previously described (Shahin et al, 2020). Briefly, 100 µL of 20 exponential growth strains were mixed evenly with 10 mL semisolid LB medium and overlaid on the LB Agar (1.5% agar).…”
Section: Determination Of the Lytic Activity Of The Phages Against Clinical Isolates Of E Colimentioning
confidence: 99%
“…Understanding the genetic information of phage is essential for the safe and efficient clinical application (Shahin et al, 2020). All three isolated phages lacked harmful genes, such as lysogenic genes, antimicrobial resistance, and bacterial virulence, suggesting that they met the first criterion for phage therapy (Shahin et al, 2020).…”
Section: A B D Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten microliters of the phage suspension (10 9 PFU mL − 1 ) was spotted onto double-layered BHI agar plates of each host strains (Additional le 1, Table S1). After an overnight incubation, the plates were checked for appearance of clear plaque (++), cloudy plaque (+) or no plaque (−).The e ciency of plating assay (EOP) was carried out against the Shigella isolates as described previously [27]. The EOP of the phage on their primary host strain (reference host) was considered as 1 and EOP of each strain were calculated as the ratio of phage titer on the tested bacterium to the phage titer on the reference host.…”
Section: Host Rangementioning
confidence: 99%